Synthesis, Crystal Structure, and Characterization of Two Novel One‐ and Two‐Dimensionally Polymeric Copper(II) Phosphonoacetates - Köferstein, Roberto; Arnold, Michael; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2017)
Blue single crystals of Cu[μ2‐OOC(CH2)PO3H]·2H2O (1) and Cu1.5[μ3‐OOC(CH2)PO3]·5H2O (2) were prepared in aqueous solution. In compound 1 [space group C2/c (no. 15) with a = 1623.3(2), b = 624.0(1), c = 1495.5(2) pm, β = 122.45(1)°], Cu is coordinated by three oxygen atoms stemming from the hydrogenphosphonoacetate dianion and three water molecules to form a distorted octahedron. The Cu–O bonds range from 190.4(3) to 278.5(3) pm. The connection between the Cu2+ cations and the hydrogenphosphonoacetate dianions leads to a two‐dimensional structure with layers parallel to (101). The layers are linked by hydrogen bonds. In compound 2 [space group P1 (no. 2) with a = 608.2(1), b = 800.1(1), c = 1083.6(1) pm, α = 94.98(1)°, β = 105.71(1)°, γ = 109.84(1)°], two crystallographically independent Cu2+ cations are coordinated in a square pyramidal and an octahedral fashion, respectively. The Cu–O bonds range from 192.9(2) to 237.2(2) pm. The coordination of the phosphonoacetate trianion to Cu(1) results in infinite polyanionic chains parallel to [100] with a composition of {Cu(H2O)[OOC(CH2)PO3]}nn–. Hydrated Cu(2) cations are accommodated between the chains as counterions. 1 and 2 show structural features of cation exchangers. Magnetic measurements reveal a paramagnetic Curie‐Weiss behavior. Compound 2 shows antiferromagnetic coupling between Cu2+ ions due to a super‐superexchange coupling. The UV/Vis spectra of 1 suggest three d–d transition bands at 763 nm (2B1 → 2E), 878 nm (2B1 → 2B2), and 1061 nm (2B1 → 2A1). Thermoanalytical investigations in air show that compound 1 is stable up to 165 °C, whereas decomposition of 2 begins at 63 °C.